EFEK PENAMBAHAN JUS DAUN SIRIH (Piper bettle linn) SEBAGAI ADITIF PAKAN TERHADAP PERFORMA AYAM PETELUR - Nining Haryuni; Eko Widodo; Edhy Sudjarwo (Universitas Nahdlatul Ulama Blitar, 2017)
Development of poultry has been done in terms of breeding, feeding and management. However, the implementation still faces many challenges such as the problem of production decrease. One cause of the decline in production is a health disorder caused by pathogenic bacteria (Salmonella sp and Escherichia coli). One way to overcome the problem is the use of Piper bettle linn Juice as a feed additive. The purpose of this study is to determine the effect of Piper bettle linn Juice as a feed additive to the performance of laying hens. The method used is the biological test of laying hens age 69 weeks of Isa Brown Strain of 250 laying hens, using Completely Randomized Design (RAL) with 5 treatments and 5 replications. The results of the research showed that Piper bettle linn Juice gave no significant effect (P> 0,05) to feed consumption and mortality. Influence significantly (P<0,01) to Hen Day Production (HDP), egg weight and Feed Conversion Ratio (FCR).